STRATEGI PENGEMBANGAN DESA-DESA PESISIR DI KECAMATAN PALANGGA SELATAN KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - , TRI RIANTI AGUSTIN SELONINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development strategy of coastal villages is tremendously needed to anticipate the constraints of plan and implementation of the coastal regional development. This research is conducted in the sub-district of Palangga Selatan which is intended to (1) identify the characteristics of the coastal villages, (2) know the potency and the problem contained in the coastal villages, and (3) arrange the regional development strategy based on the potency and the characteristic of the coastal villages. The methodology used in this research is survey method, whereas the analysis technique used in this research is the analysis of qualitative descriptive, quantitative descriptive, the analysis of normative and the analysis of SWOT. The result of this research shows that the coastal villages have areas almost equal between the land and the hill, have the variety of tourism potential and a lot of coastal natural resources, however the abundant of natural resources in the coastal villages are less supported by the quality of the adequate human resources, therefore ,it is needed 4 main strategies, namely: (1) the development of the natural resources of the sea, (2) the improvement of capacity and capability of the human resources and the improvement of practical knowledge of community resources in the coastal villages, (3) The development of potential of marine fishery, (4) as well as giving help the fisherman communities fishing gear.